MEMBANGUN ECOLITERANCY DAN PENEGAKAN HUKUM PERSAMPAHAN DI KABUPATEN LOMBOK TENGAH - siti rowi s,pd; Abdul Abdul Rahman; Elsawuri Raya Asrijati (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
Abstract. Garbage, especially in urban areas, is a complicated problem. There are so many problems that arise due to mismanagement of waste, ranging from social, environmental to health problems. So the purpose of this study is to provide learning to build awareness of the environment and law enforcement on waste affairs. This research uses descriptive research method with qualitative approach. Data collection method with interviews, observations and literature studies. (1) The waste problem is complex. Environmental crises and disasters, including waste in them, are carried out with relationship patterns that prioritize dominance towards values and behaviors that prioritize conservation, cooperation, and emphasize the quality of relationship patterns that respect each other, complement and maintain environmental sustainability. (2) Strict law enforcement by establishing Waste Bylaws and Regional Waste Agencies. (3) Community-based waste management can be of economic value with innovation and creation that can benefit from the future. Keywords: learning, management, innovation, waste